PENGARUH KARAKTERISTIK KOMITE AUDIT DAN PROPORSI DEWAN KOMISARIS WANITA TERHADAP PRAKTIK MANAJEMEN LABA RIIL - Safira Samsiah, (2021)
The issue of earnings management as a financial scandal has become a public concern, especially on corporate governance as an internal control mechanism to ensure the quality of financial reporting. This study aims to determine the relationship between the characteristics of the audit committee and the proportion of female commissioners to determine the relationship between internal control mechanisms and real earnings management in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Using multiple linear regression with quantitative methods and secondary data on 131 companies. Researchers detect real earnings management using the Cohen and Zarowin (2010) model, the characteristics of the audit committee are seen based on the size of the audit committee, audit committee tenure, and audit committee expertise based on the Financial Services Authority Regulation No.55/PJOK.04/2015. The results found are that the size of the audit committee has a significant effect on real earnings management, but there is no significant effect between audit committee tenure and audit committee expertise on real earnings management. In addition, there is a significant effect of the proportion of female commissioners on real earnings management